2021
DOI: 10.1177/0193945920986907
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Mild Cognitive Impairment, and Interventions for Sleep Improvement: An Integrative Review

Abstract: Sleep disturbance in mild cognitive impairment (MCI) is associated with progression to Alzheimer’s disease (AD), more severe AD symptoms, and worse health outcomes. The aim of this review was to examine the relationship between sleep and MCI, and the effectiveness of sleep improvement interventions for older adults with MCI or AD. An integrative review was conducted using four databases, and findings were analyzed using an iterative process. Findings from 24 studies showed that alterations in sleep increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Timely recognition of neurocognitive impairment is essential in optimizing prevention strategies and treatment options [ 20 ]. However, to get an early diagnosis of this condition it is necessary to know what to look for and above all where to look which means, in other words, that it is fundamental to have a comprehensive knowledge of the risk factors associated with cognitive decline, in such a way as to be able to design, apply and implement appropriate screening programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Timely recognition of neurocognitive impairment is essential in optimizing prevention strategies and treatment options [ 20 ]. However, to get an early diagnosis of this condition it is necessary to know what to look for and above all where to look which means, in other words, that it is fundamental to have a comprehensive knowledge of the risk factors associated with cognitive decline, in such a way as to be able to design, apply and implement appropriate screening programs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a number of studies suggested that sleep disturbance is predictive of cognitive decline in older people and in those with neurodegenerative disorders and such problems should be identified and treated early to prevent a deterioration of cognitive functions [ 19 , 20 ]. Indeed, several studies conducted under laboratory settings, investigating the potential effects of total or partial sleep deprivation on cognition, showed a wide range of cognitive alterations [ 7 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Burke et al (2018) found that individuals who experienced sleep disturbance had a 1.39 times higher risk of developing mild cognitive impairment compared to individuals without sleep disturbance. Poor sleepers also have cortical thinning in areas of their brains associated with mild cognitive impairment (Torossian et al, 2021). Furthermore, sleep problems affect the frontal cortex, which predominantly controls fluid cognitive tasks (Bugg et al, 2006), and in one study, fluid cognitive task scores predicted everyday function (Dassel & Schmitt, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…While we did not assess napping in this study, future research should also consider examining napping as a sleep variable that could be associated with cognitive function. Objective and subjective sleep measures are not often congruent (Rowe et al, 2008; Torossian et al, 2021); therefore, it may be useful to examine whether the outcomes would be similar using objective sleep measures. Moreover, we did not assess the length of time caregivers had sleep disturbance or their sleep disturbance relative to when they began providing care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation